Antifungal effects of the nonlinear pharmacokinetics of cilofungin, a 1,3-beta-glucan synthetase inhibitor, during continuous and intermittent intravenous infusions in treatment of experimental disseminated candidiasis. - Walsh, T J (1991)
Cilofungin (LY-121019) is a fungicidal cell wall-active 1,3-beta-glucan synthetase inhibitor with a short plasma half-life and saturable nonlinear plasma pharmacokinetics. To optimize the in vivo efficacy of this compound, we studied the effects of its linear and nonlinear pharmacokinetics during continuous versus intermittent intravenous infusion of cilofungin in the treatment of experimental disseminated candidiasis in persistently granulocytopenic rabbits. Six groups of rabbits were studied, untreated controls (n = 32) and five cilofungin dosage regimen groups consisting of the following: 25 mg/kg of body weight intravenously twice daily (VLoINT) (n = 9); 50 mg/kg twice daily (LoINT) (n = 9); 90 mg/kg twice daily (HiINT) (n = 11); 5 mg/kg/h for 18 h/day (LoCI) (n = 7); and 10 mg/kg/h for 18 h/day (HiCI) (n = 7). All regimens achieved plasma concentrations exceeding the MIC for Candida albicans (0.25 microgram/ml). In vitro timed kill assays found that the fungicidal activity and rate of kill by cilofungin above the MIC for C. albicans was concentration dependent. At the lower dosage regimens (VLoINT, LoINT, and LoCI), cilofungin followed linear plasma pharmacokinetics, whereas at higher doses (HiCI and HiINT), nonlinear kinetics consistent with a saturated elimination pathway(s) were observed. Only HiCI and HiINT produced a 10(3)- to 10(4)-fold reduction in CFU per gram in candidiasis of the brain (P less than or equal to 0.001). HiCI and HiINT also significantly reduced infection in the choroid (P less than or equal to 0.05). All regimens, except VLoInt, significantly (P less than or equal to 0.01) reduced tissue infections in lung, liver, spleen, and kidney. However, only the regimens with nonlinear saturation kinetics (HiCI and HiINT) produced a 10(6) reduction in the spleen and a > 10(5) reduction of C. albicans in the kidney and liver. A simple doubling of the dosage from LoCI to HiCI resulted in tissue concentrations that were 10 times higher and a 10(2)- to 10(4)-fold-greater antifungal effect. There was a direct correlation (r2 = 0.83) between tissue concentrations of cilofungin and antifungal activity. Thus, continuous and intermittent infusion dosage regimens that elicit nonlinear saturation plasma pharmacokinetics of cilofungin were associated with increased antifungal activity against experimental disseminated candidiasis.